Islamic Entrepreneur Resilience Model: Retail Business Survives During Crisis - Junusi, Rahman El; Mubarok, Ferry Khusnul (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Covid-19 affects all sectors, including micro, small and medium enterprises. The purpose of this study is to determine the factors that affect the resilience of Muslim retail entrepreneurs and to develop models of entrepreneurial strength in the face of crises due to Covid 19. The research sample used 160 Muslim retail entrepreneurs who are members of the Sampoerna Retail Community (SRC). The analytical techniques used are factor analysis and SEM model testing with AMOS. From the results of the factor analysis, there are six variables, namely resilience capacity entrepreneurship, customer orientation, retailer's attitude, social capacity, Islamic Spirituality and digital marketing that affect the resilience of Muslim retail entrepreneurs. The model developed shows that social capital is not significant in explaining the resilience capacity of Muslim retail entrepreneurs. For that, we need encouragement, support, coaching and support to empower retail business businesses.